STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI USAHA MIKRO KECIL DAN MENENGAH (UMKM) OLEH DINAS KOPERASI UKM KOTA PEKANBARU - Fani Balqis; Tuti Khairani Harahap (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Micro, Small, And Medium Enterprises (MSMEs) are one of the backbone of national’s economy. There are obstacles to development MSMEs in Pekanbaru City, such as low quality of human resources on MSMEs, and the weakness of MSMEs understanding in business license. This research aimed to analyse how much effort the Cooperatives, Small, and Medium Enterprises Office of Pekanbaru City to empower society through MSMEs, and to know the inhibiting factors to empower citizens. The research based on Strategy Of Society Empowerment theory by Kartasasmita. The qualitative research method used to collect data by interview, observation, and documentation and use a purposive sampling techniques. The data analysis techniques use descriptive qualitative. The result of this reasearch is that efforts in several aspects about society empowerment by Cooperatives Small And Medium Enterprises Office of Pekanbaru City has been done but it is still not maximal enough. The recommendations in this research for Cooperatives Small And Medium Enterprises Office of Pekanbaru City to increase the quantity of human resources, so it can be reach all of MSMEs in Pekanbaru City, to give supports to MSMEs, and for MSMEs to apply the business license as an empowerment access. Keywords: Strategy, Society Empowerment.